Analytic Network Process-Based Cluster Head Selection Mechanism for Extending the Network Lifetime - A, Amuthan; A, Arulmurugan (International Journal of Computer Sciences and Engineering, 2019)
The role of wireless sensor networks is considered to be evolving ubiquitous in the present day life due to its suitability and applicability in surveillance, weather forecasting and implantable sensors used for the purpose of health monitoring and other diversified number of applications. The use of tiny sensor nodes in WSN results in the crucial issues of restricted energy, limited energy and computation time. In this context, the network lifetime expectancy purely depends on the efficient and effective utilization of available resources in the network. However, the organization of sensor nodes into clusters is essential for the potential management of each and every cluster as well as the complete network. In this paper, Analytic Network Process-based Cluster Head Selection Mechanism (ANP-CHSM) is proposed for the objective of the cluster head selection with the view to enhance the network expectancy. This proposed ANP-CHSM considered the parameters that are associated with Residual Energy of Sensor Nodes (RESN), Distance between Nodes (DBN), merged node, Frequency Count in Cluster Head Role (FC-CHR) and Centroid Distance of Sensor Nodes (DSN) for modelling the process of cluster head selection. This proposed ANP-CHSM scheme aided in the optimal cluster head selection process by tackling the aforementioned parameters that attribute towards multi criteria decision making processes. The simulation results of the proposed ANP-CHSM was also considered to be significant over the compared cluster head selection frameworks contributed for effective clustering-based lifetime improvement processes.